VIOLENCE AGAINST WOMEN. LATIN AMERICAN THEORETICAL PERSPECTIVE - MEJÍA-NAVARRETE , Julio (2024)
The article exposes the theoretical developments on violence against women in Latin America. Examines the order of male domination that imprints its permanence in social history, the current modern colonial patriarchal pattern that organizes gender relations is analyzed, to explain the structuring of female violence and finally investigate the expansion of the mafia parastatality of the social life.